Purple grumixama anthocyanins (Eugenia brasiliensis Lam.) attenuate obesity and insulin resistance in high-fat diet mice. Issue 8 (1st April 2021) - Teixeira, Luciane de L.; Pilon, Geneviève; Coutinho, Camille Perella; Dudonné, Stéphanie; Dube, Pascal; Houde, Vanessa; Desjardins, Yves; Lajolo, Franco M.; Marette, André; Hassimotto, Neuza M. A.
Abstract : The anthocyanins from the purple grumixama phenolic extract is responsible for reducing obesity and insulin resistance. Abstract : Some polyphenols have been reported to modulate the expression of several genes related to lipid metabolism and insulin signaling, ameliorating metabolic disorders. We investigated the potential for the polyphenols of two varieties of grumixama, the purple fruit rich in anthocyanins and the yellow fruit, both also rich in ellagitannins, to attenuate obesity-associated metabolic disorders. Mice were fed a high fat and high sucrose diet, supplemented daily with yellow and purple extracts (200 mg per kg of body weight) for eight weeks. Purple grumixama supplementation was found to decrease body weight gain, improve insulin sensitivity and glucose-induced hyperinsulinemia, and reduce hepatic triglyceride accumulation. A decrease in intrahepatic lipids in mice treated with the purple grumixama extract was associated with lipid metabolism modulation by the PPAR signaling pathway. LPL, ApoE, and LDLr were found to be down-regulated, while Acox1 and ApoB were found to be upregulated. Some of these genes were also modulated by the yellow extract. In addition, both extracts decreased oGTT and plasma LPS. The results were associated with the presence of phenolic acids and urolithins. In conclusion, most likely the anthocyanins from the purple grumixama phenolic extract is responsible for reducing obesity and insulin resistance.